Immediate two-stage tissue expander breast reconstruction compared with one-stage permanent implant breast reconstruction: A multi-institutional comparison of short-term complications. Issue 5 (October 2013) - Davila, Armando A.; Mioton, Lauren M.; Chow, Geoffrey; Wang, Edward; Merkow, Ryan P.; Bilimoria, Karl Y.; Fine, Neil; Kim, John Y. S.
Abstract Prosthesis-based techniques are the predominant form of breast reconstruction worldwide, with two-stage tissue expander procedures being the most popular. In the past decade, there has been increasing interest in performing single-stage implant reconstruction immediately following mastectomy as an attempt to simplify the reconstructive course and improve psychosocial morbidity. However, there is a paucity of large-scale, multi-institutional data comparing the outcomes of these two reconstructive strategies. Patients who underwent immediate tissue expander or implant reconstruction following mastectomy from 2006–2010 were identified using standardised operation codes. Demographic information for patients, 30-day outcomes, and adverse events for each type of reconstruction were analysed and compared between groups. A total of 10, 561 patients underwent immediate breast reconstruction. There were 9033 patients who underwent tissue expander placement (2752 bilateral), and 1528 patients who underwent immediate implant placement (485 bilateral). Patients who had implant placement demonstrated increased rates of overall complications (6.8% compared with 5.4%, p = 0.02) and prosthesis failure (1.4% compared with 0.8%, p = 0.04). There was no difference in the rate of any surgical site infections (3.9% compared with 3.4%, p = 0.39), reoperation (7.5% compared with 6.9%, p = 0.40), or major medical complications (1.8% compared with 1.6%, p = 0.57). Both immediate one-stage, direct-to-implant, and two-stage tissue expander reconstructions result in low rates of morbidity. One-stage reconstruction suggests a slightly higher complication rate related to prosthesis failure.